A Schanuel property for j - Eterović, S (Wiley, 2018)
I give a model-theoretic setting for the modular j function and its derivatives. These structures, here called j-fields, provide an adequate setting for interpreting the Ax-Schanuel theorem for j of J. Pila and J. Tsimerman. Following the ideas of M. Bays, J. Kirby and A. J. Wilkie for exponential fields, I prove a generic transcendence property for the j function.